2021
DOI: 10.1038/s41588-020-00759-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel ACE2 isoform is expressed in human respiratory epithelia and is upregulated in response to interferons and RNA respiratory virus infection

Abstract: ith more than 53 million confirmed cases of COVID-19 and 1.3 million associated deaths worldwide (World Health Organization, 13 November 2020), there is an urgent need to understand the molecular mechanism of infection and disease to identify patients' susceptibilities and targets for therapeutic intervention. ACE2 is the main viral entry point for coronavirus N63, SARS-CoV and SARS-CoV-2, which cause severe acute respiratory syndromes, the last being responsible for COVID-19 in humans 1-4. ACE2 binds to the S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
130
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(159 citation statements)
references
References 73 publications
11
130
1
1
Order By: Relevance
“…2a). Immunoblotting confirmed detection of the correct molecular mass of ~110/120 kDa and recently reported 12,49 short 50-kDa isoforms of endogenous ACE2 in both cell types (Extended Data Fig. 2b).…”
Section: Ace2 and Tmprss2 Expression In Endocrine Cells And A Ductal Subpopulationsupporting
confidence: 80%
See 2 more Smart Citations
“…2a). Immunoblotting confirmed detection of the correct molecular mass of ~110/120 kDa and recently reported 12,49 short 50-kDa isoforms of endogenous ACE2 in both cell types (Extended Data Fig. 2b).…”
Section: Ace2 and Tmprss2 Expression In Endocrine Cells And A Ductal Subpopulationsupporting
confidence: 80%
“…Fignani et al 12 provide a comprehensive analysis on ACE2 expression in β-cells, including mass-spectrometry-based detection. Briefly, this study showed that the short ACE2 isoform is expressed in human pancreatic islets, where it is preferentially expressed in subsets of insulin-producing β-cells 12,49 . It is interesting also that Kusmartseva et al reported detectable mRNA levels of ACE2 in a proportion of endocrine cells 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the absence of a transcriptional response to secreted interferon cannot be explained by a lack of either interferon alpha receptor ( IFNAR1, IFNAR2 ) or interferon gamma receptor ( IFNGR1, IFNGR2 ) expression. Previous work has identified ACE2 , the host receptor for SARS-CoV-2, as among the interferon-induced genes in nasal epithelial cells, with uncertain significance for SARS-CoV-2 infection 29,8183 . Indeed, we find modest upregulation of this gene among cells from COVID-19 participants compared to healthy controls.…”
Section: Resultsmentioning
confidence: 99%
“…Southeast Asians have greater body fat than Europeans and North Americans for the same BMI, meaning Southeast Asians cannot be treated as obese despite their larger visceral fat amounts [27]. It has been shown that the SARS-CoV-2 virus uses angiotensin-converting enzyme 2 (ACE2) as a gateway into the body [28][29][30]. ACE2 is a cell-surface exoenzyme that converts angiotensin II (Ang II) into vasodilatory angiotensin 1-7 (Ang 1-7).…”
Section: The Obesity Paradox Visceral Fat and Covid-19 Outcomesmentioning
confidence: 99%